2010
DOI: 10.1007/s12291-010-0070-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoproterenol on Tissue Defense Enzymes, Hemodynamic and Left Ventricular Contractile Function in Rats

Abstract: Present study investigated the effects of isoproterenol-induced oxidative stress on hemodynamic and ventricular functions in rats. Subcutaneous injections of isoproterenol (85 mg/kg for two consecutive days at 24 h interval) significantly decreased myocardial antioxidant enzymes; superoxide dismutase, catalase and glutathione peroxidase in heart. Isoproterenol-induced oxidative stress was also evidenced by significant depletion of reduced glutathione and increased formation of lipid peroxidation product, thiob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…However, rosuvastatin (5 mg/kg) significantly alleviated the pathophysiological and morphologic changes including cardiac myocyte hypertrophy, inflammatory cell infiltration, interstitial fibrosis which strongly demonstrated the protective effect of rosuvastatin on ventricular remodeling and hypertrophy in isoproterenol‐induced heart failure rats. The changes of LVSP, LVdP/dt max and LVdP/dt min reflected an overall dysfunction between myocardial contractility and relaxation . Present investigation demonstrated that treatment with 5 mg/kg isoproterenol for 7 days caused significant changes in levels of LVSP, LVdP/dt max , SAP, MAP, HR and LVdP/dt min in rats, which were in line with previous research results .…”
Section: Discussionsupporting
confidence: 92%
“…However, rosuvastatin (5 mg/kg) significantly alleviated the pathophysiological and morphologic changes including cardiac myocyte hypertrophy, inflammatory cell infiltration, interstitial fibrosis which strongly demonstrated the protective effect of rosuvastatin on ventricular remodeling and hypertrophy in isoproterenol‐induced heart failure rats. The changes of LVSP, LVdP/dt max and LVdP/dt min reflected an overall dysfunction between myocardial contractility and relaxation . Present investigation demonstrated that treatment with 5 mg/kg isoproterenol for 7 days caused significant changes in levels of LVSP, LVdP/dt max , SAP, MAP, HR and LVdP/dt min in rats, which were in line with previous research results .…”
Section: Discussionsupporting
confidence: 92%
“…The myocardial damage produced by isoproterenol is irreversible in nature and occurs via free radical generation due to auto-oxidation and positive inotropic and chronotropic effect. Since hemodynamic, ventricular, biochemical, morphological, and histopathological changes following high dose isoproterenol administration in rats resemble closely to those occurring in patients with myocardial infarction, the isoproterenol-induced MI serves as a well-standardized model to study the beneficial effects and mechanism of many drugs [ 19 , 21 - 23 ]. As anticipated, in the present study, isoproterenol administered rats showed hemodynamic and ventricular dysfunction as evident by decreased contractility and relaxability and elevated preload as compared to sham group.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in arterial pressure values, viz., systolic blood pressure, diastolic blood pressure and MABP against an increasing HR indicates deranged sympathetic and parasympathetic inputs to the heart. It is possible that a deteriorating myocardial contractility following ISO administration might be responsible for a significant fall in MABP, a marker of afterload (Ojha et al ., ). Similarly, a deterioration in myocardial relaxation followed by ISO administration is responsible for an increase in LVEDP that is a surrogate marker of preload.…”
Section: Discussionmentioning
confidence: 97%